It could have been otherwise : contingency and necessity in Dominican theology at Oxford, 1300-1350 - Gelber, Hester Goodenough, 1943- (Studien und Texte zur Geistesgeschichte des Mittelalters ;, 2004)
"This volume deals with the Dominicans at Oxford University from 1300-1350. It describes the history of the Oxford friary, who the friars were, who were there, how they were chosen and the intellectual life they created. It develops the idea of the friary as a "conversational community."" "It's readership will include those interested in intellectual history, history of philosophy, history of theology, medieval history, history of the university, Oxford university, history of the Church, Dominicans, medieval logic and modal theory."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved